Active Control of Nonlinear Suspension System Using Modified Adaptive Supertwisting Controller. (14th July 2015) - Rath, Jagat J.; Veluvolu, Kalyana C.; Defoort, Michael
Abstract : The suspension system is faced with nonlinearities from the spring, damper, and external excitations from the road surface. The objective of any control action provided to the suspension is to improve ride comfort while ensuring road holding for the vehicle. In this work, a robust higher order sliding mode algorithm combining the merits of the modified supertwisting algorithm and the adaptive supertwisting algorithm has been proposed for the nonlinear active suspension system. The proposed controller is robust to linearly growing perturbations and bounded uncertainties. Simulations have been performed for different classes of road excitations and the results are presented.